2018
DOI: 10.1097/jnr.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Maternal Characteristics and Postpartum Hemorrhage: A Meta-Analysis Study

Abstract: Midwives, obstetric nurses, and obstetricians should carefully evaluate mothers for the risk factors of PPH during the antepartum, intrapartum, and postpartum periods. Moreover, at-risk pregnant women should give birth in a unit with emergency initiative options. Future studies should examine relevant personal characteristics of mothers, as familiarity with the risk factors facilitates the management and treatment of PPH. Finally, meta-analyses should review more studies to detect risk factors more comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 2 publications
2
33
0
5
Order By: Relevance
“…14,15 However, the study by Durmaz et al revealed that no relationship between maternal age ≥35 years old and PPH. 5 This study discovered that maternal age with the highest percentage was 20-35 years old (57.5%). Previous study by Driessen et al had the same result that the highest women with PPH is 20-35 years old.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…14,15 However, the study by Durmaz et al revealed that no relationship between maternal age ≥35 years old and PPH. 5 This study discovered that maternal age with the highest percentage was 20-35 years old (57.5%). Previous study by Driessen et al had the same result that the highest women with PPH is 20-35 years old.…”
Section: Discussionmentioning
confidence: 79%
“…Contrary to this study, the previous studies revealed that primiparity is one of risk factors for PPH. 5,16,18 About 69.45% of PPH occurred to the patient with gestational age 37-42 weeks (term pregnancy). This study showed the same result with two previous studies that found most of the women with PPH is in 37-42 weeks pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Durmaz and Komurcu found no such relationship in their meta-analysis, which included includs five studies and 1,286,752 women. 3 In fact, Lao and colleagues also pointed that advanced maternal age only served as a surrogate factor for PPH due to the associated increased risk factors, obstetric complications and interventions. 4 Their multivariate analysis indicated that aging was actually associated with decreased PPH, the risk decreasing progressively from those aged 25-29 years to those aged ≥40 years compared with the 20-24 years group.…”
Section: Discussionmentioning
confidence: 99%
“…3 Perdarahan postpartum adalah penyebab utama kematian ibu di Negara dengan penghasilan ekonomi yang rendah dan penyebab utama satu dari setiap empat kematian ibu di seluruh dunia. 4 Salah satu upaya proses kehamilan dan persalinan dapat berjalan lancar dan tanpa ada komplikasi dan penyullit. Ibu hamil di anjurkan agar melaksanakan senam selama kehamilan sebagai upaya preventif agar kehamilan dan persalinan berjalan secara alami dan mengurangi resiko cidera akibat persalinan.…”
Section: Pendahuluanunclassified